Exploring literacies theory, research and practice - De Silva Joyce, Helen; Feez, Susan (Research and practice in applied linguistics, 2016)
"Exploring Literacies: Theory, Research and Practice is a guide to research and debate in the field of literacies education. The book traces three possible pathways through the vast terrain of research and practice. Section 1 introduces five orientations to the teaching of literacy and explores the role of literacy in human societies over time, including the development and teaching of specialised fields of knowledge. Section 2 examines the teaching and learning of literacies across the human lifespan, including the foundations of literacy in early childhood, the link between literacy and learning of educational knowledge during the school years, and the literacy demands of adult life. Section 3 reviews a range of methods used to research literacy in social contexts in general and in education in particular. This section concludes with the voices of literacy researchers describing first-hand their literacy research experiences. With a detailed overview of the research field of literacy teaching, development and professional research, this book will be invaluable for teacher educators and students of Education, TESOL, Literacy or Applied Linguistics"--Provided by publisher.